Self-efficacy and therapeutic adherence in adults with type 2 diabe- tes mellitus at the Daniel Alcides Carrión National Hospital - Lima 2016 - Cribillero-Roca, Miriam (2019)
Objective. To determine the relationship between self-efficacy and therapeutic adherence. Methods. A correlational study was carried out with 85 patients from the Daniel Alcides Carrión - Lima National Hospital, during the 2016 period. A self-efficacy scale and a adherence to treatment questionnaire were used. The Pearson r coefficient was used in the inferential analysis. Results. 54.1% (46 patients) had low self-efficacy and 38.8% (33 patients) had poor treatment adherence. In addition, there was a rela- tionship between self-efficacy and therapeutic adherence, with p≤0,000. And, likewise, self-efficacy is significantly related to therapeutic adherence in pharmacological treatment (p≤0,000), diet (p≤0,000) and physical exercise (p≤0,000). Conclusions. There was a relationship between self-efficacy and therapeutic adherence in adults with type 2 diabetes mellitus at the Daniel Alcides Carrión National Hospital - Lima.